Muslims Of Surma-Barak Valley In The Partition Of 1947 - Dr. Mahbubur Rahman Laskar (International Journal of Advanced Science and Technology, 2020)
Few events have been more important to the history of modern South Asia than the partition of subcontinent in to India and Pakistan in 1947. Whether partition was inevitable or was there any alternative, has been a matter of debate since independence. Partition of India in 1947 was not a sudden event or occurrence, but certain forces, elements and agencies generated the situation that made Partition inevitable. Surma-Barak Valley presently constituted the three districts of Barak Valley viz. Cachar, Karimganj and Hailakandi and broader Sylhet presently constituted with Habiganj, Sunamganj, Maulabi Bazar and Sylhet districts of Bangladesh, which was a part of Assam sub-division faced this division. Physical division took place in the eastern and western side of the Indian sub continent. Sylhet was separated from the rest of the province and attached with the East Pakistan. Of course political leaders and parties commanded the matter and they tried to approach the Muslim masses to bring under their respective banner. They too used religious leaders and religion symbolically to get the mass support in the referendum. Muslim of Surma-Barak valley, thus were divided broadly in to two groups – one is under Jamiat Ulema Hind, allied of Indian National Congress and the other under Muslim League. Dialogues, songs, poems were composed by both the groups to convince the people and to raise the sentiment of the other section of Muslim. So, the issue of the partition of the country led to the contradictory stands of the Muslims of Surma-Barak Valley.